2018
DOI: 10.1038/s41526-018-0051-2
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to an extreme environment comes at a sensorimotor cost

Abstract: Long duration space flight is known to induce severe modifications in the sensorimotor and musculoskeletal systems. While in-flight strategies including physical fitness have been used to prevent the loss of bone and muscle mass using appropriate rehabilitative countermeasures, less attention has been put forth in the design of technologies that can quickly and effectively assess sensorimotor function during missions in space. The aims of the present study were therefore (1) to develop a Portable Sensorimotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…We calculated each ML displacement by double integration with high-pass filtering of the resulting acceleration from sensors donned at the head, upper trunk, and pelvis, respectively [25,30]. The amount of ML displacement was quantified by the area under the ML displacement curve [27]. In this study, an increase in the area indicated decreased upper body balance control [31].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We calculated each ML displacement by double integration with high-pass filtering of the resulting acceleration from sensors donned at the head, upper trunk, and pelvis, respectively [25,30]. The amount of ML displacement was quantified by the area under the ML displacement curve [27]. In this study, an increase in the area indicated decreased upper body balance control [31].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we measured the sagittal plane angular velocities from each ankle (gyroscope), defined as a rotation in the sagittal plane. The data was then processed and interpreted through the dynamic time warping (DTW)-based algorithm [27] that precisely quantifies the movement difference of each gait stride signal during TW.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants completed questionnaires regarding demographic information. The body worn sensor system that we currently use is comprised of five wireless MTw IMUs, Xsens shirt, and Velcro straps (Xsens Technologies, Netherlands) [26][27][28]. In this study, acceleration and angular velocities along three perpendicular axes data were analyzed from three IMUs (chest and each ankle) during the TUG test.…”
Section: Test Procedures and Data Acquisitionmentioning
confidence: 99%